Underwater Bubble and Oil Repellency of Biomimetic Pincushion and Plastron-Like Honeycomb Films - Chen, Bihai (Langmuir : the ACS journal of surfaces and colloids, 2020)
Underwater highly bubble and oil-repellent surfaces were prepared based on honeycomb- and pincushion-structured films prepared by breath figure technique and post modifications including UV-ozone treatment and peeling the top layer. Furthermore, bubble generation from the plastron-like honeycomb gas chamber by attaching oil droplet onto the surface of honeycomb films was first observed. Both controlling gas bubbles and oil droplets underwater are important issues in the field of microfluidics since they are useful and may solve the maleficence to liquid transportation in narrow microchannels